Ergonomic Design of Medical Record Document Storage Room at Puskesmas Yosowilangun - Moordhaya, Dhela Kalis; Roziqin, Mochammad Choirur; Alfiansyah, Gamasiano; Prakoso, Bakhtiyar Hadi (International Journal of Healthcare and Information Technology, 2024)
The size of the filing room at the Yosowilangun Health Center is not yet up to standard, the medical record document shelves, work tables and chairs are not ergonomic. The research aims to create an ergonomic design for the filing room at the Yosowilangun Health Center. This type of research is qualitative, using interview, documentation, observation, and brainstorming data collection techniques. The results of the research are that there is a need to design a new filing room that is adapted to standard regulations. The design of work desks, work chairs, and medical record document shelves is adjusted based on the anthropometry of the staff. The number of new filing shelves needed is calculated using the IFHIRO (International Federation Health Record Organization) formula. The area of the new filing room is 36m2, consisting of active and inactive filing rooms.